Strong absorption in ultra-wide band by surface nano engineering of metallic glass - Jianan Fu; Xin Li; Zhen Li; Fei Sun; Wenxin Wen; Jinlai Zhao; Wenqing Ruan; Shuai Ren; Zhenxuan Zhang; Xiong Liang; Jiang Ma (Fundamental Research)
Broadband light absorption is important for applications such as infrared detectors, solar energy collectors, and photothermal conversion. We propose a facile and common strategy to fabricate light absorbers with strong ultra-wideband absorption. Due to their excellent thermoplastic forming ability, metallic glasses could be patterned into finely arranged nanowire arrays, which show extremely low reflectivity (∼0.6%) in the visible and near-infrared regimes, and a low reflectivity (∼15%) in the mid-infrared regime as caused by multiscale nano spacing, multiple reflections, and plasmonic behavior. The strong absorption at surfaces with nanowires provides excellent photothermal conversion properties. The photothermal properties show that a surface with nanowires can be rapidly heated up to ∼160 °C at a rate of 28.75 °C/s, which is 30 times higher than smooth surfaces. Meanwhile, a surface with nanowires shows a high photothermal conversion efficiency (ηPT = 56.36%). The fabricated metallic glass absorbers exhibit adaptability as they can be easily formed into various complex shapes and meet the requirements under harsh conditions. The outcomes of our research open the door to manufacturing high-performance absorbers for applications in photothermal electric power generation, desalination, and photodetectors.